Dental Prosthetic Status and Prosthetic Need of the Institutionalized Elderly Living in Geriatric Homes in Mangalore: A Pilot Study. (7th October 2010) - Shenoy, Rekha P.; Hegde, Vijaya
Abstract : Introduction . To promote oral health among the elderly, we need to know their prosthetic status and prosthetic need. Hence, a survey of prosthetic status and need of elderly inmates of old age homes in Mangalore was done. Materials and Methods . A cross-sectional study was undertaken, and 133 subjects aged 60 years and above were examined (54.9% males and 45.1% females). Results . Eighty-eight percent of those examined were fully edentulous, and only 12% had complete dentures; none of the study subjects had partial dentures. Prosthetic status was significantly associated with gender (P = .024 ), while prosthetic need and gender were not significantly associated (P = .395 ). Conclusions . A high unmet need for prosthetic care existed among the institutionalized elderly surveyed.